The State of the Banking System of Northern Bukovyna and Khotyn Region in the Interwar Period - Rusnak, Oleksandr (Chernivtsi National University, 2020)
In this article the author describes the state of the banking system of Northern Bukovyna and Khotyn region in 1918-1940 in the amalgamation of royal Romania. The attention is paid to the development of bank offices and main directions of their work. The stress is laid on negative results of World War I for the financial system of region; the period of rising of bank sphere in 1920s is investigated in details. The influence of Great depression on work of region’s banks is characterized. Its main manifestations are analyzed.
Keywords: banks, Northern Bukovyna, Khotyn region, inflation, monetary unit, credit, capital, deposit